How Accurately Should We Model Ice Shelf Melt Rates?. Issue 1 (8th January 2019) - Goldberg, D. N.; Gourmelen, N.; Kimura, S.; Millan, R.; Snow, K.
Abstract: Assessment of ocean‐forced ice sheet loss requires that ocean models be able to represent sub‐ice shelf melt rates. However, spatial accuracy of modeled melt is not well investigated, and neither is the level of accuracy required to assess ice sheet loss. Focusing on a fast‐thinning region of West Antarctica, we calculate spatially resolved ice‐shelf melt from satellite altimetry and compare against results from an ocean model with varying representations of cavity geometry and ocean physics. Then, we use an ice‐flow model to assess the impact of the results on grounded ice. We find that a number of factors influence model‐data agreement of melt rates, with bathymetry being the leading factor; but this agreement is only important in isolated regions under the ice shelves, such as shear margins and grounding lines. To improve ice sheet forecasts, both modeling and observations of ice‐ocean interactions must be improved in these critical regions. Plain Language Summary: The Antarctic coastline is fringed by large floating ice shelves, often the size of cities or larger. They play a crucial role as a stopgap against acceleration of the ice sheet, and their loss could lead to considerable sea level rise. Many of these ice shelves are exposed to warm waters from farther north, leading to considerable melting underneath. Scientists use models of the ice sheet and the ocean in order to understand the link between warming oceans and sea levels, and how this might change in the future. In our study we focus on one of these fast‐thinning ice shelves and determine through satellite imagery that melting is not uniform across the ice shelf but is highly focused in certain areas due to ocean currents. Using state‐of‐the‐art ice and ocean models, we investigate what information will be needed in order to predict how the Antarctic Ice Sheet will respond to climate change. Our findings suggest that improved knowledge of ocean depth under ice shelves, as well as improved understanding of ocean flow just below the ice bottom, will be vital in determining the effects of climate change on ice shelves and ice sheets. Key Points: Satellite measurement of melt rates shows high spatial variability under two fast‐flowing ice shelves Ice‐sheet response to ice shelf melt depends on the pattern of melt rates as well as their spatial average The ability of an ocean model to reproduce this pattern depends on accurate bathymetry and ice shelf draft data